State punishment : political principles and community values - Lacey, Nicola (International library of philosophy., 2002)
Nicola Lacey presents a new approach to the question of the moral justification of punishment by the State. She focuses on the theory of punishments in context of other political questions, such as the nature of political obligation and the function and scope of criminal law. Arguing that no convincing set of justifying reasons has so far been produced, she puts forward a theory of punishments which places the values of the community at its centre.